Metabolic Basis for Nonlinearity in 1, 3-Dichloropropene Toxicokinetics and Use in Setting a Kinetically-derived Maximum Inhalation Exposure Concentration in Mice. (6th December 2019) - Bartels, Michael J; Hackett, Michael J; Himmelstein, Matthew W; Green, John W; Walker, Carl; Terry, Claire; Rasoulpour, Reza; Challender, Mary; Yan, Zhongyu (June)
Abstract: 1, 3-Dichloropropene (1, 3-D) showed a statistically increased incidence of bronchioloalveolar adenomas in male B6C3F1 mice at 60 ppm air concentration during previous chronic inhalation testing. No tumors were observed in female mice, nor in either sex of F344 rats up to 60 ppm, the highest dose tested. Therefore, to understand if lung tumors observed in high dose male mice are due to saturation of metabolic clearance, the linearity of 1, 3-D concentrations in mouse blood was investigated on day 15 of repeated nose-only inhalation exposure to 0, 10, 20, 40, 60, 90, and 120 ppm (6 h/d, 7 d/week). Additional groups were included at 20, 60, and 120 ppm for blood collection at 1.5 and 3 h of exposure and up to 25 or 40 min post-exposure to determine area-under-the-curve. The data provide multiple lines of evidence that systemic exposures to 1, 3-D in the mouse become nonlinear at inhalation exposure levels of 30 ppm or above. A reduction in minute volume occurred at the highest exposure concentration. The glutathione (GSH)-dependent metabolism of 1, 3-D results in significant depletion of GSH at repeated exposure levels of 30 ppm and above. This loss of GSH results in decreased metabolic clearance of this test material, with a concomitant increase of the 1, 3-D isomers in circulating blood at exposure concentrations ≥30 ppm. Shifts in the ratio of cis - and trans -1, 3-D also support nonlinear toxicokinetics well below 60 ppm. Based on this data, a kinetically derived maximum dose for 1, 3-D in mice for repeated exposures should be at or below 30 ppm. These results support non-relevance of 1, 3-D-induced benign pulmonary tumorigenicity in mice for human health risk assessment.